THE RELATIONSHIP BETWEEN FAMILY SUPPORT WITH LEVEL OF DEPRESSION IN THE ELDERLY AT PANTI WERDHA MOJOPAHIT MOJOKERTO - Sajidin, Muhammad; Anwar, Khoirul (JURNAL KEPERAWATAN BINA SEHAT, 2011)
Many changes due to modernization cause some problems related to elderly care. Workload of children because of their profession or other activities consuming almost entire time. This condition makes elderly more neglected socially, culturally and psychologically. Panti Werdha as elderly nursing home becomes an option for families to care for the elderly. The research objective is to analyze the relationship between family support with level of depression in the elderly at Panti Werdha Mojopahit Mojokerto. Research design is analytical correlation with cross sectional approach. Population is all elderly who still have families as amny as 37 people and it’s taken 32 peopole as samples by purposive sampling. The independent variable is family support and dependent variable is level of depression in elderly. Data is collected using family support questionnaire and Geriatric Depression Scale (GDS-15), then analyzed using Spearmans rho. Research result shows that mostly have negative family support as many as 20 respondents (62.5%) and mostly have moderate level of depression as many as 12 respondents (37.5%). Spearmans rho test result shows ρ (0.002) <α (0.05), means H0 is rejected, so relationship between family support with level of depression in the elderly at Panti Werdha Mojopahit Mojokerto. The r value = -0.530 shows negative correlation and moderate relationship, means that higher family support, lower level of depression in the elderly. Psychological problems as lonely and useless which are caused by less family support are important factors that could make depression for those who lived in elderly nursing home. Elderly should learn more about various coping patterns that can be used to relieve symptoms of depression and learn to accept their condition right now. Health personnel should constantly monitor and collaborate with psychiatry to deal with severe depression.Key words: family support, depression, elderly